Pylosanid disease: Modified Buie marsupialization technique - Sapriza, Carlos (Cirugía del Uruguay, 1979)
A review of Marsupializatio'n technique (Buie's operation) for the treatment of pil'onidal disease, is accompanied by statistics. This technique is easy to carry out, can be applied universally, recurrency of condiiton is low and post-operatory morbility is discreet.